Finerenone: a mineralocorticoid receptor antagonist for the treatment of chronic kidney disease associated with type 2 diabetes. Issue 5 (4th May 2022) - Lerma, Edgar V.; Wilson, Daniel J.
ABSTRACT: Introduction: Approximately 40% of people with type 2 diabetes (T2D) also have chronic kidney disease (CKD), which substantially increases their risk of cardiovascular (CV)-related complications and mortality. Until recently, no approved therapies have directly targeted inflammatory and fibrotic pathways that drive disease progression and organ damage in patients with CKD associated with T2D. Areas covered: Finerenone is a potent, selective, nonsteroidal mineralocorticoid receptor antagonist (MRA) that targets fibrosis and inflammation by blocking overactivation of the MR in the kidneys and heart. Finerenone has been associated with significant reductions in kidney- and CV-related endpoints compared with placebo and minimal effects on serum potassium and kidney function in phase III trials involving >13, 000 patients with diabetic kidney disease (DKD). In addition to reviewing the clinical data, this review compares the properties of finerenone with those of the older steroidal MRAs spironolactone and eplerenone. Expert opinion: Unlike spironolactone and eplerenone, finerenone has demonstrated a favorable benefit-risk profile offering an effective new treatment for patients with CKD associated with T2D. Increases in serum potassium are predictable and manageable and should not discourage the use of finerenone in clinical practice. It is important to discuss where finerenone 'fits best' within the current DKD management landscape.